A Very Bright, Very Hot, and Very Long Flaring Event from the Young Nearby M Dwarf Binary DG CVn - Osten, Rachel A.; Drake, Stephen Alan; Kowalski, Adam; Krimm, Hans A.; Page, Kim; Gazeas, Kosmas; Kennea, Jamie A.; Oates, Sam; Page, Mat; Gehrels, Neil (American Astronomical Society Meeting Abstracts #227, 2016)
On April 23, 2014, the Swift satellite responded to a hard X-ray transient detected by its Burst Alert Telescope, which turned out to be a stellar flare from a nearby, young M dwarf binary DG~CVn. Observations at X-ray, UV and optical wavelengths of the main impulsive flare and subsequent smaller events reveal a complex pattern of flare events extending over about three weeks. We find that the X-ray spectrum of the primary outburst can be adequately described by either a single very high temperature plasma or a nonthermal thick-target bremmstrahlung model. By evaluating accompanying data of this event and analysis of a second brightening, we argue that the thermal interpretation is more likely on energetic grounds. The primary outburst lasted a few hours and produced the highest temperature thermal plasmas ever seen spectroscopically over the 0.3-100 keV range in a stellar flare, at TX of 300 MK. The X-ray luminosity of the main flare exceeded the bolometric luminosity of the brighter component (LX >1.6Lbol) for ~360 seconds. The first event was followed by a comparably energetic event almost a day later, whose coverage at X-ray and optical wavelengths enables inferences about it and the first event. In particular we find evidence for stellar radius-sized coronal loops filled with dense (ne>1012 cm-3) coronal plasma. The radiated energy in X-rays and white light reveal these first two events to be some of the most energetic X-ray and white light flares from an M dwarf. These structures require large coronal magnetic field strengths (a few kG for the first event, hundreds of Gauss for the second) to confine the plasma, and we thus predict an extremely high photospheric magnetic field strength of several kiloGauss.